THE REPRESENTATIVITY OF THE HIGH HEEL - Conceicao Attab, Renan Martins da [UNESP]; Fernandes, Priscila da Silva [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This work aims to understand how high heels have been present for so long in the socio-cultural evolutionary process, addressing the consequences that this type of footwear produced, especially in the work environment, demystifying the power of fascination it causes in women and understanding the issue of the male fetish with respect to that object. As a methodology, a research was carried out in which historical facts, blogs and scientific articles were analyzed for theoretical development. As a result, it was found that the use of high heels in daily life can be very harmful to the spine and legs of women and that the use of these shoes is the result of a machoistic culture, based on the fetishism of the male imagination.
Keywords: High heels; Fetish; Power